Salicylic acid in nutrient solution influence the fruit quality and shelf life of cherry tomato grown in hydroponics - Mohammad Zahirul Islam; Mahmuda Akter Mele; Choi, Ki-Young; Jun, Pill Baek; Kang, Ho-Min (Penerbit Universiti Kebangsaan Malaysia, 2018)
Salicylic acid (SA) is a plant hormone that has functional effects in plant. This study was conducted to find out the effects of salicylic acid (SA) on cherry tomato fruit quality and shelf life. Different concentrations (0.13, 0.25, 0.50 and 1.00 mM) SA were added in nutrient solution of hydroponic system in plants vegetation and fruits development stage. Light-red maturity stage of cherry tomato fruits was harvested to measure the harvest time fruit quality and stored at 5℃ to measure the postharvest quality and shelf life. Ethylene production and respiration rate of tomato fruit at the harvest time and after storage was effectively reduced by the 0.50 mM SA treatment. Increased acetaldehyde (p≤0.05) as well as ethanol (p≤0.001) was performed in the 0.50 mM SA treatment at after storage. The 0.50 mM SA treatment showed the lowest fresh weight loss 3.08% and the longest shelf life 25 days by reducing decay, fruits softening and fungal infection. Significantly lower fungal incidence (p≤0.001) was observed in the 0.50 mM SA treatment. Final storage day color development and lycopene content was lower in the 0.50 mM SA treatment compare with other treatments. The 0.50 mM SA treatment obtained the highest firmness at harvest time and it retain after storage. Comparatively higher vitamin C and lower soluble solids was showed at the harvest time and after storage. Therefore, the 0.50 mM SA treatment is effective in increasing the quality and shelf life of cherry tomato fruit.